Analysis daily newspaper distribution in Solo by Agent Based Simulation. (May 2019) - Febriandini, Izatul Fitria; Yuniaristanto,; Sutopo, Wahyudi; Hisjam, Muhammad
Abstract: Agent based simulation is a simulation model that can be used to describe the interaction between the involved agents. The interaction is generated from observations of human behavior. This study aims to provide an overview of business process PT Aksara Solopos and involved agents in it, especially for Koran Harian Solopos. In addition, to cope with the large number of paper returns is estimating the newspaper demand by simulation. Simulations done using NetLogo 6.0.3 applications. This research produced the number of clients who are subscribed by newspaper deliveryman and daily stock for the company, newsagents, newspaper deliveryman to complete the consumer demand.